Specific features of comorbidity in rheumatoid arthritis patients in different follow-up years - N. M. Nikitina; I. A. Afanasyev; T. A. Romanova; A. P. Rebrov (Современная ревматология)
Objective: to study the rate and pattern of comorbidities in two groups of patients with rheumatoid arthritis (RA) in different follow-up years.Subjects and methods. The pattern of comorbidity was investigated in RA patients treated at the Rheumatology Unit, Saratov Regional Clinical Hospital, in different follow-up years. The investigation enrolled patients treated with disease-modifying antirheumatic drugs (DMARDs) in a stable dose for 3 months or longer. The patients were interviewed and objectively examined and the data of their outpatient medical records were taken into consideration. Group included 201 patients examined in 2006–2007. Group 2 comprised 328 patients examined in 2012–2013.Results. Comorbidities were ascertained in 67.2% of the patients in Group 1 and in 86.6% of those in Group 2. Two to five co-occurring diseases were more common in the examinees in 2012–2013 (66.9%) than in those in 2006–2007 (57%). The patients of both groups were most frequently found to have hypertension (60 and 57.7% of the patients, respectively) and osteoarthritis (OA) (71.1 and 50.7%). Out of the other diseases, the patients were most commonly found to have gastrointestinal tract (GIT) diseases (97.8 and 80.3%, respectively) and urinary tract infections (22.4% and 19.7%).Conclusion. The rate of comorbidities remains high in patients with RA. Among the comorbid diseases, there is a preponderance of hypertension, GIT diseases, and OA.